Influences on story development in transnational pan-Arab dramas: A case study of the series 04. (1st June 2019) - Haddad, Fadi G.
Despite the growing research interest in the transnational nature of the Arab World's television industry, screenwriting in the Arab World has received little academic attention. Moreover, while the media plays a major role in shaping the 'narratives of identity', the reality of television drama production is as much about cultural, economic and political influences as it is about aesthetics. Set within a unique interpretation of the theoretical context of the 'Hierarchy of Influences Model', this article aims to explore to what extent the routine practices in screenwriting govern the artistic decisions taken at the level of the screenplay development of transnational pan-Arab dramas (Arabic: al-drāma al 'arabiya al-mushtaraka). Taking '04' (Zero Four) as a case study, a pan-Arab drama produced by the Saudi-owned UAE-based MBC television that tells the story of four young expatriates from four different Arab nationalities living in modern-day Dubai, and through in-depth interviews with the show creators, the article attempts to present an example of novel screenwriting practices in the Arab World between single authors and writers' room.